ANALISIS KARAKTERISTIK PERUSAHAAN DAN PERGANTIAN AUDITOR TERHADAP RESTATEMENT - Victoria Ari Palma Akadiati (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2018)
This empirically study to analyze the characteristics company and change of auditors of therestatement on the companies listed on the Indonesia Stock Exchange from 2007 until 2011. Thecharacteristics of the company include the size of the company, the company's profitability as measuredby ROA (return on assets), leverage measured using DER (debt to equity ratio).The data used in this study were 506 sample companies listed on the Indonesia StockExchange. The hypothesis in this study was tested by means of logistic regression analysis usingsoftware tools SPSS 17.00.The results show that firm size variables significantly influence the accounting restatements andother variables such as profitability, leverage and change of auditors has no effect. Implications,limitations and suggestions will be discussed further in this study